A study on the problems facing by G1 and G2 contractors in Malaysia - Afiqah Farhana, Zamani (2017)
The increase in the number of contractors substantially parallel to the development in Malaysia. In 2016, the number of registered contractor have increase and become 74,188 compared with 2015 only 71,799 registered contractor in Malaysia (CIDB, 2016). These improvements have enhanced competition among contractors and increase the risk of having to close down. There are many factors that affect an increasing number of contractors in Malaysia, which is the result of government efforts to improve the development of Malaysia through the 9th Malaysia Plan. Therefore, the objective of this study was to investigate the economic growth in the construction sector in Malaysia, to identify factors that encourage an increasing number of G1 and G2 contractors in Malaysia and to analyze the problems faced by contractors in handling their business. Apart from literature review on the issue, several questionnaires have been sent out based contractors of Class G1 and G2. All data can be gathered through the questionnaire will be analyzed using the average index to answer the third research objective of analyzing the problems faced by contractors in the conduct of their business. To facilitate the process of analyzing, Statistical Package for Social Science (SPSS 16.0 for Windows) software and Microsoft Excel software were used. The analysis shows that the increasing numbers of contractors is closely link to the development of the construction industry. The factors increasing the construction industry is the country's economic performance, financial facilities, demographic growth and inflation. Besides that, this study showed that there are a few aspects of problems faced by the contractor which are financial, construction material, economic, financial facilities, workers and heavy machinery. Generally, the respondents believe that the biggest problem is related with workers and heavy machinery aspects with an average index of at most 3.09. However, the study found that this problem can still be controlled.